Are Firm Capabilities Holding Back Firms in Mozambique? - Aga, Gemechu; Campos, Francisco; Conconi, Adriana; Davies, Elwyn; Geginat, Carolin (World Bank, Washington, DC, 2021)
Firm capabilities—the abilities and practices to operate and innovate—are considered important drivers of firm performance. While the analysis of their importance is well established in developed countries, its study in the African context is more recent. The paper uses a new representative sample of enterprises in Mozambique comprising data on management and organizational practices, as well as skills, to study the importance of firm capabilities in Mozambique. The analysis suggests that the private sector in Mozambique scores below other developing countries in all dimensions of firm capabilities. Enterprises engaging in more contractual relationships demonstrate stronger firm capabilities. Firm capabilities are key drivers of performance; controlling for other input factors, firms in Mozambique with better firm capabilities perform better. The relationship is robust to various measures of performance and to including various firm and manager characteristics. The analysis finds that for smaller firms, non-exporters, and female-owned enterprises, their gap in business performance can be explained by differences in management practices. The results suggest Mozambique should explore mechanisms of expanding firm capabilities in targeted types of firms.